Recent Research on Human Papillomavirus (HPV) Infection and Vaccination (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Persistent infection with high-risk human papillomavirus is associated with virtually all cervical cancers and a significant proportion of anogenital and oropharyngeal cancers. In recent years, significant progress has been made in cervical cancer prevention, especially in terms of the availability of prophylactic vaccines. However, the HPV vaccine has not yet achieved full coverage, and rates have dropped during the COVID-19 pandemic. It is therefore necessary to strengthen HPV vaccine education, vaccination and early prevention, especially in situations such as in low-income countries, where there are still multiple issues related to its dissemination and acceptance. Meanwhile, exploring the various aspects underlying the mechanism of progression of HPV-associated malignancies, host immune system reactions toward HPV viruses as well as HPV vaccination is important for the development of specific therapeutics and vaccines against viral clinical manifestations. Research areas of the Special Issue include discussing the knowledge and attitudes surrounding prophylactic HPV vaccination; vaccination implementation; effective instruments or interventions to improve public awareness of HPV vaccination; improving equity in HPV vaccination; the impact of the COVID-19 pandemic on HPV vaccination; host factors related to HPV infection, persistent, cervical intraepithelial neoplasia, and cervical cancer; co-infection of HPV with other pathogens; progression of HPV-associated malignancies; HPV and host–virus interaction; novel HPV vaccine development.